HUBUNGAN PENGETAHUAN TENTANG FAKTOR RISIKO PJK DENGAN PERILAKU PENCEGAHAN TERJADINYA PJK - Silviana, Hanny Ika Virgo; Sipollo, Berliany Venny; Sulartri, Anastasia Sri; Sakti, Ifa Pannya (Jurnal Keperawatan Malang, 2025)
Background: The knowledge that families possess helps them adopt effective preventive behaviors to protect elderly individuals with hypercholesterolemia from coronary heart disease. Purpose: This study aimed to determine the relationship between knowledge of coronary heart disease risk factors and preventive behaviors of coronary heart disease among families of elderly individuals with hypercholesterolemia in RW 10, Bandungrejosari Village, Malang City. Methods: This study was a quantitative research using a correlational method. A total of 50 respondents were selected as samples using the total sampling technique. The respondents were given a questionnaire, and the data were analyzed using Spearman's Rho correlation test. Result: The correlation test results show a p-value of 0.014 (p < 0.05), indicating that the study reveals a relationship between knowledge about coronary heart disease risk factors and preventive behavior for coronary heart disease.